2005
DOI: 10.1155/2005/297472
|View full text |Cite
|
Sign up to set email alerts
|

Lung Function Measured by Impulse Oscillometry and Spirometry Following Eucapnic Voluntary Hyperventilation

Abstract: IOS is an acceptable measure to determine AHR and can supplement spirometry in lung function evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
3
11
2
1
Order By: Relevance
“…The latter provides an alternative method for measuring and monitoring lung function and is advantageous in that the test is non-effort dependent and potentially evaluates small airway function. The technique has previously been found to be an acceptable measure to supplement spirometry following EVH (39)(40)(41). The current study indicates that IOS variables appear to exhibit a similar degree of variability to spirometry following EVH, and as such does not support the notion of superiority when employed to assess airway calibre in this setting.…”
Section: Discussioncontrasting
confidence: 62%
“…The latter provides an alternative method for measuring and monitoring lung function and is advantageous in that the test is non-effort dependent and potentially evaluates small airway function. The technique has previously been found to be an acceptable measure to supplement spirometry following EVH (39)(40)(41). The current study indicates that IOS variables appear to exhibit a similar degree of variability to spirometry following EVH, and as such does not support the notion of superiority when employed to assess airway calibre in this setting.…”
Section: Discussioncontrasting
confidence: 62%
“…In addition, IOS has previously been identified to correlate with both FEV1 [88,89] and airway resistance [90,91] as determined by spirometry and body plethysmography respectively. Specific to EIB, IOS has been shown to be an acceptable measure to supplement spirometry following EVH [92]. In support of these findings, Evans and colleagues observed strong correlations between spirometry and IOS variables.…”
Section: Impulse Oscillometrymentioning
confidence: 83%
“…Although Rundell et al (13) reported strong correlations between IOS variables (resistance and reactance) and ∆FEV1max following EVH, the study consisted of only twenty subjects with (n = 10) and without (n = 10) a previous diagnosis of airway hyper-responsiveness (AHR). In addition, the average reduction in lung function following EVH for individuals with a positive diagnosis was significantly greater (30.6%) i.e.…”
Section: Indeed the Implications Of Over And Under-diagnosis Of Airwamentioning
confidence: 99%
“…Evans et al (11) observed a change in airway function following room temperature and cold air exercise challenges that would have otherwise remained undetected by spirometry. The conclusion from a series of studies (11)(12)(13) was that IOS yields greater sensitivity for detecting changes in airway function in athletes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation